Yahoo Web Search

  1. ... for me to type/copy/paste: Solving for " u ": a = (1 - u ) / √(1 - u²) start out by ...2(1 ± a²) / [2(a² + 1)] 2's cancel out: u = (1 ± a²) / (a² + 1) Now let's split...

    3 Answers · Science & Mathematics · 17/05/2015

  2. ...t know the answer? But anyway this is the way you do it... 277=178- u every time you swap a number to the other side of the '=' (equal) sighn...

    5 Answers · Science & Mathematics · 01/03/2008

  3. Let u = v cos(r) v^3 cos^3(r) + 3 v cos(r) = 39 - 3cos(t) Multiply by 4 and...2/3)pi n + (1/3)arccos([ 39 - 3cos(t) ] (3i/2)) Now you know that u = v cos(r) So u = 2i cos[ (2/3)pi n + (1/3)arccos([ 39 - 3cos(t...

    1 Answers · Science & Mathematics · 12/11/2016

  4. Let u =x-2. Then, x= u +2 and dx = du Then, \int 5x/(x-2)^(1/2) dx becomes \int 5( u +2) * u ^(-1/2) du= 5\int ( u ^(1/2)+2 u ^(-1/2)) du= 5 (2/3 u ^(3/2)+ 4 u ^(1...

    3 Answers · Science & Mathematics · 02/08/2006

  5. u = x^2 + 24 du = 2x * dx x^3 * sqrt(x^2 + 24) * dx => x^2 * sqrt(x^2 + 24) * x * dx => ( u - 24) * sqrt( u ) * (1/2) * du => (1/2) * u ^(3/2) * du - 12 * u ^(1/2) * du ...

    1 Answers · Science & Mathematics · 24/11/2013

  6. u = x - 3 Derive implicitly du = dx - 0 du = dx So, x = u + 3 u = x - 3 and du = dx x * (x - 3)^(5/2) * dx =>...7 * u ^(2/2) + 3 * 9 * 1) + C => (2/63) * (7u + 27) * u ^(7/2) + C => (2/63) * (7 * (x - 3) + 27) * (x - 3...

    3 Answers · Science & Mathematics · 28/04/2013

  7. Hi U -substitution is the inverse of the chain rule. However, as it is... multiplied so you can go from ∫ f(g(x)) * g'(x) dx to ∫ f( u ) du (notice that if you apply the chain rule to F( u ), the integral of f( u ), you...

    1 Answers · Science & Mathematics · 05/02/2011

  8. 1) ∫ u sqrt(1- u ^2) du Let t=1- u ^2 dt = -2udu u du = (-1/2) dt ∫ u sqrt(1- u ^2) du = (-1/2...x^3) / x^(8/2) dx = ∫ sqrt(1-3/x^3) / x^4 dx Let u = 1-3/x^3 u =-3 x^(-3) du=(-3)(-3) x^(-4) du = 9/x^4 dx 1...

    3 Answers · Science & Mathematics · 03/08/2013

  9. Alright... U generally look for the deepest buried function to call variable " u "...bracket, lets make u =cosx...Notice sin x is outside the bracket.. u =cosx du/dx= -sinx Differentiate implicitly du= -sinx dx...

    1 Answers · Science & Mathematics · 10/05/2008

  10. u ^2 = -2u + 15 u ^2 + 2u - 15 = 0 u ^2 + 5u - 3u - 15 = 0 u ( u + 5) - 3( u + 5) = 0 ( u - 3)( u + 5) = 0 u - 3 = 0 or u + 5 = 0 u = 3 or u = -5 If u = 3 we have: 3 = sqrt(-2*3 + 15) 3 = sqrt(-6 + 15) 3 = sqrt(9) TRUE If u = -5...

    4 Answers · Science & Mathematics · 10/06/2016

  1. Ad
    related to: U
  1. Try asking your question on Yahoo Answers